2022
DOI: 10.47191/ijsshr/v5-i12-96
|View full text |Cite
|
Sign up to set email alerts
|

Male and Female Lecturers’ Politeness Strategies in Academic Interaction

Abstract: The aim of this research was to identify the types of politeness strategies used by male and female lecturer during the classroom interaction, and to find out the target achieve by the male and female lecturer in using politeness strategy. The researcher has chosen four English lecturer (two male and two female) at Universitas Muhammadiyah Makassar. The researcher joined in the class and recorded the activities when lecturer was teaching. The researcher applied descriptive qualitative method to analyze the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Adopting politeness strategies shortens the teacher-student social distance, makes the class more interesting and facilitates English teaching and learning. Another research conducted by Fattah, Qalbi & Dewi (2022), found that male and female lecturers used four politeness strategies to create cooperative interaction and help the students to have positive feelings towards lessons as well as to motivate them to participate actively during class interaction. The previous study focused on what types of politeness strategies the teachers used and the reasons why they used politeness strategies during their interactions in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Adopting politeness strategies shortens the teacher-student social distance, makes the class more interesting and facilitates English teaching and learning. Another research conducted by Fattah, Qalbi & Dewi (2022), found that male and female lecturers used four politeness strategies to create cooperative interaction and help the students to have positive feelings towards lessons as well as to motivate them to participate actively during class interaction. The previous study focused on what types of politeness strategies the teachers used and the reasons why they used politeness strategies during their interactions in the classroom.…”
Section: Introductionmentioning
confidence: 99%